Azores, Atlantic, and Diaspora - Scott, D.; Borges, D.; Fonseca, A. M.; Monteiro, A. (The Azores, the Atlantic, and the global challenges: Geopolitics and diaspora, 2024)
The Archipelago of the Azores, strategically situated in the North Atlantic, holds a significance that extends far beyond its striking volcanic landscapes. Its geographical location has rendered it a crucial point of interest during pivotal moments in history, such as World War II and the Cold War. Serving as a vital stopover for military and commercial flights and a key hub for submarine communications cables, the Azores has been indispensable in global connectivity and security. In contemporary times, the archipelago remains a significant player in international relations and assumes a vital role in extending Portugal’s domain in Atlantic security. As global political dynamics shift and new challenges emerge, the islands’ strategic location continues to be of paramount importance.